The National Johne's Management Plan: using risk and data analysis to optimise Johne's control in dairy herds. (2nd January 2022) - Orpin, Pete Guy; Sibley, Dick; Hanks, James; Taylor, Nick
Abstract : The National Johne's Management Plan (NJMP) is now a compulsory element of the Red Tractor Farm assurance scheme. Over 95% of UK dairy farms will need to undertake surveillance, risk assessments, and have a written veterinary control plan, and 70% of participants are utilising milk enzyme-linked immunosorbent assay (ELISA) testing. To support the NJMP a new Johne's Progress Tracker has been developed that uses key outcome measures and drivers to provide new insights into Johne's disease (JD) development. Benchmark measures have been developed allowing for graphical comparison of all measures. The JD Tracker delivers a practical opportunity to help JD veterinary advisors to evaluate the reasons why their herds are succeeding or failing to control JD. The development of enhanced risk assessment tools is also essential to identify the expanded list of risks, and engaging the farmer with a successful JD control plan helps secure the farmer's prospects.